Assessment of Long Distance Chasing Photometer (NAG-ADF-300-2) by Estimating the Drug Atenolol with Povidone Iodine Via CFIA - Mezaal, Elham N.; Turkey, Nagam S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
Atenolol was used with povidone iodine to prove the efficiency, reliability and repeatability of the long distance chasing photometer (NAG-ADF-300-2) using continuous flow injection analysis. The method is based on reaction between atenolol and povidone iodine in an aqueous medium. Optimum parameters was studied to increase the sensitivity development of method. Calibration graph was linear in the range of 2-19 mmol/L for cell A and 5-19 mmol/L for cell B. Limit of detection 146.4848 ng/55 µL and 2.6600 µg/200 µL respectively to cell A and cell B. Correlation coefficient (r) 0.9957 for cell A and 0.9974 for cell. Relative standard deviation (RSD %) was lower than 1%, (n=8) for the determination of atenolol at concentration (5, 9 and 17) mmol/L for cell A and (5, 13 and 17) mmol/L for cell B respectively. The results were compared with classical method UV-spectrophotometric at λ max=270 nm by using method standard addition via t-test, at 95% confidence level. The comparison of data explain that long distance chasing photometer (NAG-ADF-300-2) is the choice with excellent extended detection and wide application.